2000
DOI: 10.2307/177209
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Tortoise Life History: Demography of Gopherus berlandieri

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ecological Society of America is collaborating with JSTOR to digitize, preserve and extend access to Ecology.Abstract. Turtles provide excellent models for studies of life his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…The population of P. oculifer at Benfontein was skewed towards adults, which is similar to that recorded for many other testudinid populations (for example see Van Heezik et al 1994;Hellgren et al 2000;Lagarde et al 2001). A high predation rate of juveniles and a low probability of finding them were both considered plausible reasons for low juvenile catches of Stigmochelys pardalis and Chersina angulata in the Eastern Cape (Mason et al 2000).…”
Section: Life History Traitssupporting
confidence: 84%
See 3 more Smart Citations
“…The population of P. oculifer at Benfontein was skewed towards adults, which is similar to that recorded for many other testudinid populations (for example see Van Heezik et al 1994;Hellgren et al 2000;Lagarde et al 2001). A high predation rate of juveniles and a low probability of finding them were both considered plausible reasons for low juvenile catches of Stigmochelys pardalis and Chersina angulata in the Eastern Cape (Mason et al 2000).…”
Section: Life History Traitssupporting
confidence: 84%
“…The dearth of males in older cohorts may indicate that the smaller body size of males makes them more predation prone. In a population of Gopherus berlandieri, Hellgren et al (2000) found that females, which mature earlier and are smaller than males, predominate in younger cohorts with the bias switching to males in older generations. The authors gave differential predation rates as one of the possible causes of fewer females in older generations.…”
Section: Life History Traitsmentioning
confidence: 96%
See 2 more Smart Citations
“…However, there have been few evidences for this characteristic in reptil species, according to Iverson (1979), Iverson et al (1991), Redrobe & Scudamore (2000) and Hellgren et al (2000).…”
Section: Discussionmentioning
confidence: 99%